ADVANTAGES OF USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN INFORMATICS AND IT SCIENCES - Z. K. Ilyasova; N. B. Utebaeva (Journal Park Publishing, 2025)
This article will analyze the advantages of using artificial intelligence (SI) technologies in Computer Science and IT. Artificial intelligence allows for a personalized approach to computer science and IT in the educational process, the introduction of automated assessment systems, the analysis of students' knowledge in real time, and the development of interactive and innovative teaching methods.
Keywords: Artificial intelligence, digital learning, adaptive learning, automated assessment, educational technologies, interactive learning, innovative learning, inclusive education.